BUILDING KNOWLEDGE FROM HOME: A TRANSFORMATIVE TEACHING EXPERIENCE DURING PANDEMIC TIMES. - Gladis Ángela Corredor (DIALÉCTICA, 2026)
Faced with the digital divide at the "Valentín García" Educational Institution in Labranzagrande (Boyacá) during the pandemic, "Building Knowledge from Home" was implemented. This strategy ensured meaningful learning for Elementary students through non-technological resources. This article documents and shares how this pedagogical experience transformed the institution’s technological limitations into innovative opportunities, offering educational communities a hopeful model that demonstrates that the best connectivity is not 4G, but the bond between school, family, and territory. The methodology integrated five actions: 1) design of printed guides with a constructivist approach linked to daily experiences; 2) support through calls, audio messages, and optional virtual classes; 3) enrichment activities for advanced students; 4) WhatsApp groups by grade level; and 5) community radio classes. Results showed: strengthening of collaborative work among teachers, families, and students; development of critical thinking through "learning by doing"; and revaluation of local knowledge. The initiative confirms that educational innovation emerges from limitations, transforming adversities into creative opportunities with territorial roots. It is concluded that effective pedagogy in rural contexts is woven with community resources rather than digital ones.